1981
DOI: 10.1093/oxfordjournals.jbchem.a133547
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Dependent Neutral Proteases, Widespread Occurrence of a Species of Protease Active at Lower Concentrations of Calcium1

Abstract: A species of neutral protease having high affinity for Ca2+ in the 10(-5) M range, originally found in canine cardiac muscle (Mellgren, R.L. (1980) FEBS Lett. 109, 129-133), is detected in a wide variety of rat tissues when a sensitive assay with 125I-iodinated casein as substrate is employed. This species of protease absolutely requires Ca2+, and other divalent cations are practically inactive. Although the activity of this enzyme apparently shows striking diversity among tissues tested, the enzymes obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Second, this processing was inhibited either by E-64 (a cysteine protease inhibitor) or by leupeptin (a serine and cysteine protease inhibitor). Although the reason for this partial inhibition is not known, there is a report showing that CANP in its purified form is very sensitive to leupeptin and E-64 but that crude preparations of CANP are far less susceptible to the same inhibitors (15). The possibility that other enzymes can also contribute to the proteolytic cleavage of pre-IL-la cannot be excluded.…”
Section: Discussionmentioning
confidence: 98%
“…Second, this processing was inhibited either by E-64 (a cysteine protease inhibitor) or by leupeptin (a serine and cysteine protease inhibitor). Although the reason for this partial inhibition is not known, there is a report showing that CANP in its purified form is very sensitive to leupeptin and E-64 but that crude preparations of CANP are far less susceptible to the same inhibitors (15). The possibility that other enzymes can also contribute to the proteolytic cleavage of pre-IL-la cannot be excluded.…”
Section: Discussionmentioning
confidence: 98%
“…Calpain was first isolated from porcine skeletal muscle and described by Dayton et al, 1976a;Dayton et al, 1976b. After this initial isolation of calpain, which was later named m-calpain (calpain 2), two other calpain family members were identified, m-calpain (calpain 1) and calpastatin, the endogenous inhibitor of calpain (Dayton et al, 1981, De Martino, 1981, DeMartino and Croall, 1982, Kishimoto et al, 1981, Mellgren, 1980, Murakami et al, 1981, Nishimura and Lemasters, 2001Sakon et al, 1981). Since these founding members of the calpain family were identified, numerous ubiquitous (Thompson and Goll 2000) or tissue-specific (Sorimachi et al, 1993a, Sorimachi et al, 1993bSorimachi et al, 1994) as well as vertebrate and invertebrate calpains have been identified (Goll et al, 2003).…”
Section: The Calpain Family Of Proteasesmentioning
confidence: 99%
“…72) In 1977, Yasutomi Nishizuka and his colleagues identified calpain as a protein kinase C (PKC) activating factor, 6) and several calpain studies were done in line with PKC. 73ā€“76) In 1978, Imahori and his colleagues for the first time in the world purified chicken calpain to homogeneity and called it CANP. Following this remarkable study, Imahoriā€™s group established calpain research field by publishing important studies on enzymology of calpain such as substrate specificity, 77) purification from human muscle, 78) inhibitors, 79,80) autolysis, 8,81) and activation.…”
Section: A Research History Of Calpain and Its Definitionmentioning
confidence: 99%